Narrative Murals as a Form of Offerings and Evidence of Confucian Conggregation Participation in Maintaining the Temple. : A Case Study at the Cu An Kiong Temple, Lasem, Indonesia - Burhan, Mukhamad Agus; Prasetya, Hanggar Budi; Triatmodjo, Suastiwi; Budiarti, Endah; Dar, Ku Boon (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study focuses on the question of why narrative murals are consistently present in temples, what these murals depict, and what themes they contain. A qualitative descriptive case study approach has been employed to answer these questions. Three types of data were used to study the murals: visual data in the form of the murals themselves, interviews, and documents. The findings of this study show that a narrative mural is intended as an offering to express gratitude to the gods or goddesses for the fulfilment of a family's prayers to demonstrate the congregation's participation in maintaining the temple’s existence.